Indications and outcomes of pancreatic surgery after liver transplantation. (8th February 2014) - Mejia, Juan; Sucandy, Iswanto; Steel, Jennifer; Golas, Benjamin; Humar, Abhinav; Lee, Kenneth; Zeh, Herbert; Marsh, James; Tsung, Allan
Abstract Background Prior liver transplantation and immunosuppression potentially translate into significant morbidity and poor outcomes after any type of pancreatic surgery. Little is known about the outcomes of pancreatic surgery after liver transplantation. This study was designed to review our experience regarding the indications and outcomes of pancreatic surgery following liver transplantation. Methods A retrospective review of all liver transplant recipients who underwent pancreatic surgery between 1991 and 2009 was performed. Results A total of 3196 patients underwent liver transplantation, of whom 18 (0.6%) subsequently required pancreatic surgery. The most common indications were necrotizing pancreatitis and lesions of the head and tail of the pancreas. Procedures performed included pancreaticoduodenectomy, distal pancreatectomy, and pancreatic necrosectomy. The estimated blood loss was 500 mL and operative time was 430 ± 224 min. Pathology results revealed malignant lesions in six (33%) patients, pre‐malignant lesions in 2 (11%) patients, and benign lesions in 10 (56%) patients. The median time from transplantation to pancreatic surgery was 61 months. The 30‐d postoperative complication rate was 77.8%, with median hospital stay of 15 d. The three‐, 12‐, and 24‐month survival rates were 78%, 48%, and 24%, respectively. Conclusions Pancreatic surgery after liver transplantation results in significant 30‐d complications. Prior liver transplantation, however, should not be a contraindication for subsequent pancreatic surgery, due to its decent survival outcome.